Controllable synthesis of 3D BaXO4 (X = W, Mo) microstructures by adjusting nucleation stage and their photoluminescence properties. (April 2015) - Li, Miaojing; Guan, Yue; Yin, Yongkui; Cui, Xinyu; Rong, Shengzhong; Jin, Ge; Hao, Yanhua; Wu, Qunhong
Highlights: Two simple routes are exploited to synthesize 3D BaXO4 microstructures. Adjusting reagent concentration can effectively control the morphology of 3D BaXO4 . Introducing EDTA can further effectively control the morphology of 3D BaXO4 . The two synthetic routes are all attributed to control the nucleation rate occurred in nucleation stage. Abstract: Due to high speed development of micro- or nanodevices, the requirements for their building blocks (micro- or nanostructures) with specific morphologies are more and more strict. Herein, two facile strategies are introduced to synthesize 3D BaWO4 and BaMoO4 microcrystals. By adjusting the concentration of reagents or chelate, the aspect ratios and the pod number of obtained products were successfully controlled. A series of characteristics (XRD and SEM) indicate the difference of surface energy at nucleation stage plays a crucial role in final shapes. The obtained samples (BaMoO4 and BaWO4 ) exhibited different emission intensities.